Epigenome-wide effects of vitamin D and their impact on the transcriptome of human monocytes involve CTCF - Seuter, Sabine (Nucleic Acids Res, 2016)
The physiological functions of vitamin D are mediated by its metabolite 1α,25-dihydroxyvitamin D(3) (1,25(OH)(2)D(3)) activating the transcription factor vitamin D receptor (VDR). In THP-1 human monocytes we demonstrated epigenome-wide effects of 1,25(OH)(2)D(3) at 8979 loci with significantly modulated chromatin accessibility. Maximal chromatin opening was observed after 24 h, while after 48 h most sites closed again. The chromatin-organizing protein CTCF bound to 14% of the 1,25(OH)(2)D(3)-sensitive chromatin regions. Interestingly, 1,25(OH)(2)D(3) affected the chromatin association of CTCF providing an additional mechanism for the epigenome-wide effects of the VDR ligand. The 1,25(OH)(2)D(3)-modulated transcriptome of THP-1 cells comprised 1284 genes, 77.5% of which responded only 24 h after stimulation. During the 1,25(OH)(2)D(3) stimulation time course the proportion of down-regulated genes increased from 0% to 44.9% and the top-ranking physiological function of the respective genes shifted from anti-microbial response to connective tissue disorders. The integration of epigenomic and transcriptomic data identified 165 physiologically important 1,25(OH)(2)D(3) target genes, including HTT and NOD2, whose expression can be predicted primarily from epigenomic data of their genomic loci. Taken together, a large number of 1,25(OH)(2)D(3)-triggered epigenome-wide events precede and accompany the transcriptional activation of target genes of the nuclear hormone.